Propuesta de Actualización del SG-SST para la Empresa de Servicios Públicos Progresar S.A.E.S.P del Municipio de San Antonio del Tequendama en Cundinamarca (2023)
This project is based on the development of a proposal for updating the Occupational Health and Safety management system for the company PROGRESAR SA ESP of San Antonio del Tequendama under decree 1072 of 2015 and resolution 0312 of 2019, this regulations establish all the guidelines for implementing, developing and/or updating the system, as well as compliance with minimum standards in order not to incur sanctions.